ZAMОNAVIY ZOОLОGIYA FANI TA’LIMIDA FОYDALANILADIGAN VОSITALAR VA ULARGA QO’YILADIGAN TALABLAR - Karimova , M.X. (Actual problems and prospects of the study of the fauna, 2024)
The use of computer and Information Technology in zoology tutorials provides educators with the potential to model and other similar biochemical processes that take place in living organisms.